Ultrasound Visual Biofeedback and Accent Modification: Effects on Consonant and Vowel Accuracy for Mandarin English Language Learners - Courtney Beth ARMSTRONG; Heather Leavy RUSIEWICZ; Katie MICCO; Yang CHEN (康复学报)
Objective:To examine the effect of ultrasound visual biofeedback as a primary tool in accent modification services for American English consonant and vowel targets produced by native Mandarin speakers.Methods:The biofeedback was measured by perceptual and visual analyses. A single-subject ABAB withdrawal design was employed with two adults who spoke Mandarin as their first language. Ultrasound visual biofeedback, verbal cues, and perceptual training were implemented to improve production of/r/, /I/, and/ɛ/in words.Results:Perceptual ratings by naive listeners indicated that phoneme production improved as a function of ultrasound visual biofeedback training. The participants also improved their ability to perceive phonetic differences as evidenced by quantitative analyses.Conclusion:Analyses showed that ultrasound visual biofeedback intervention improved production accuracy for American English/r/, /I/, and/ɛ/produced by two native Mandarin speakers. Additionally, there was evidence of generalization to untrained targets and more challenging contexts.